Questioning the Role of Carotid Artery Ultrasound in Assessing Fluid Responsiveness in Critical Illness: A Systematic Review and Meta-Analysis - Samuel C. D. Walker; Adam C. Lipszyc; Matthew Kilmurray; Helen Wilding; Hamed Akhlaghi (Critical Care Research and Practice)
Background. A noninvasive and accurate method of identifying fluid responsiveness in hemodynamically unstable patients has long been sought by physicians. Carotid ultrasound (US) is one such modality previously canvassed for this purpose. The aim of this novel systematic review and meta-analysis is to investigate whether critically unwell patients who are requiring intravenous (IV) fluid resuscitation (fluid responders) can be identified accurately with carotid US. Methods. The protocol was registered with PROSPERO on the 30/11/2022 (ID number: CRD42022380284). Studies investigating carotid ultrasound accuracy in assessing fluid responsiveness in hemodynamically unstable patients were included. Studies were identified through searches of six databases, all run on 4 November 2022, Medline, Embase, Emcare, APA PsycInfo, CINAHL, and Cochrane Library. Risk of bias was assessed using the QUADAS-2 and the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) guidelines. Results were pooled, meta-analysis was conducted where amenable, and hierarchical summary receiver operating characteristic models were established to compare carotid ultrasound measures. Results. Seventeen studies were included (n = 842), with 1048 fluid challenges. 441 (42.1%) were fluid responsive. Four different carotid US measures were investigated, including change in carotid doppler peak velocity (∆CDPV), carotid blood flow (CBF), change in carotid artery velocity time integral (∆CAVTI), and carotid flow time (CFT). Pooled carotid US had a pooled sensitivity, specificity, and AUROC with 95% confidence intervals (CI) of 0.73 (0.66–0.78), 0.82 (0.72–0.90), and 0.81 (0.78–0.85), respectively. ∆CDPV had sensitivity, specificity, and AUROC with 95% CI of 0.72 (0.64–0.80), 0.87 (0.73–0.94), and 0.82 (0.78–0.85), respectively. CBF had sensitivity, specificity, and AUROC with 95% CI of 0.70 (0.56–0.80), 0.80 (0.50–0.94), and 0.77 (0.78–0.85), respectively. Risk of bias and assessment was undertaken using the QUADAS-2 and GRADE tools. The QUADAS-2 found that studies generally had an unclear or high risk of bias but with low applicability concerns. The GRADE assessment showed that ∆CDPV and CBF had low accuracy for sensitivity and specificity. Conclusion. It appears that carotid US has a limited ability to predict fluid responsiveness in critically unwell patients. ∆CDPV demonstrates the greatest accuracy of all measures analyzed. Further high-quality studies using consistent study design would help confirm this.